Peran Kepemimpinan Transaksional dalam Mediasi Iklim Organisasi dan Kinerja Pegawai FPKB DPR RI - Achmad Chozin Rozikin; Zahera Mega Utama; Jubery Marwan (Indonesia Economic Journal, 2025)
This study aims to analyze the role of transactional leadership in mediating the effect of organizational climate on employee performance at the National Awakening Party Faction (FPKB) DPR RI. Transactional leadership is a leadership style that emphasizes the exchange relationship between leaders and subordinates through a system of rewards and punishments. A conducive organizational climate can improve employee motivation and performance, but the role of transactional leadership in this process still needs to be studied further. This study used a quantitative approach with a survey method involving 89 DPR RI FPKB employees as respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results showed that organizational climate has a positive and significant effect on employee performance, and transactional leadership partially mediates the relationship. This means that a good organizational climate can improve employee performance, either directly or through transactional leadership. The implication of this research shows that organizations need to create a supportive work environment, as well as apply an effective leadership style in motivating employees. In addition, rewarding and performance-based evaluation systems can be a strategy in increasing employee productivity.